A prosthetic-surgical approach for aesthetic treatment of peri-implant soft tissue defects: A case report - Jaafar, Mohamad Adib; Ali, Sharul Nisha; Mustafa, Siti Nurqissa (IIUM Journal of Orofacial and Health Sciences, 2024)
Peri-implant soft tissue defects (PSTD) in the esthetic zone affect approximately 54% cases of post-implant insertion, leading to aesthetic concerns and increasing the risk of peri-implantitis. Various surgical techniques are aimed at addressing these issues, but the outcomes can be unpredictable, especially for severely mispositioned implants. This report details a combined prosthetic and surgical approach to treat a severely angulated single central maxillary implant with mid-labial mucosal recession. A 38-year-old female expressed dissatisfaction with the implant at 21 area, which appeared elongated due to peri-implant mucosal recession of almost 4 mm. Treatment involved two phases: 1) prosthetic phase involves replacing the original crown of implant at 21 area with a temporary crown to promote mucosal growth and 2) surgical phase that involves soft tissue surgery three months later using an envelope flap technique at the recipient site and a connective tissue graft harvested from the palate. Upon three months after the surgery, full coverage with thick mucosal tissue was achieved, and a new zirconia crown was placed. The outcome remained stable throughout the nine-month follow-up. This case demonstrates that PSTD in angulated implants in the esthetic zone can be effectively treated through a combination of prosthetic and surgical modalities.